Determining causal pathogens and inflammatory state of mastitis in dairy cows via Gram staining of precipitates in milk - Suzuki, Naoki; Isobe, Naoki (Frontiers in Veterinary Science, 2025)
Early detection of bovine mastitis-causing pathogens is necessary for treatment. As culturing methods are time-consuming, a more rapid detection technique is required. This study investigated the sensitivity, specificity, and detection limit of Gram staining of milk precipitates (milk Gram stain, MGS) to detect bovine mastitis-causing pathogens in milk, as well as the potential of MGS to diagnose inflammation by counting polymorphonuclear leukocytes (PMN). MGS was performed on spontaneous mastitis cases. Culture methods were also used as reference standards to calculate the sensitivity, specificity, and bacterial load in milk to determine the detection limit of MGS. PMN in the mastitic milk were counted using Gram staining. Further, somatic cell counts (SCC), interleukin (IL)-6, IL-8, tumor necrosis factor (TNF)-α, IL-10 and serum amyloid A (SAA) concentrations in mastitic milk were measured using cell counting and enzyme-linked immunosorbent assay. The sensitivity and specificity for all pathogens were 0.62 and 0.90, for Gram-positive were 0.67 and 0.90, and for Gram-negative were 0.50 and 1.00, respectively. The detection limits for Gram-positive and Gram-negative bacteria were 1,560 and 4,680 cfu/mL, respectively. SCC were significantly positively correlated with PMN, milk IL-6, TNF-α, and SAA concentrations, whereas PMN were significantly negatively correlated with milk IL-10 concentration. Our results suggest that MGS may be applied as a rapid method to identify causal pathogens of mastitis before culture results are determined and may also estimate inflammatory status which cannot be detected with SCC. Further clinical trials are required to elucidate whether MGS is useful in clinical veterinary settings.